Liquid pleasures : a social history of drinks in modern Britain - Burnett, John, 1925-2006 (Routledge, 1999)
Liquid Pleasures is an engrossing study of the social history of drinks in Britain from the late 17th century to the present. Connecting drinks and related substances to empire as well, the book also covers the drinks revolution of the 1990s.